Farmers’ Knowledge and Acceptance of Microalgae in Almería Greenhouse Horticulture - Ángela Ruiz-Nieto; Cintia Gómez-Serrano; Gabriel Acién; Antonio J. Castro (Agronomy, 2022)
Almería horticulture in SE Spain hosts the largest concentration of greenhouses in the world and faces important environmental sustainability challenges. Microalgae-derived applications are efficient nature-based solutions as they are used for wastewater regeneration or as biostimulants and biopesticides in agriculture. However, farmers’ knowledge and acceptance of microalgae-derived applications remain unknown, which is a major barrier to its commercialization. This study explores current farmers’ knowledge and acceptance of microalgae in Almería horticulture. Results revealed that there exists a significant lack of knowledge regarding the use of microalgae agricultural-based applications. Over sixty percent of farmers indicated that microalgae can have beneficial uses in agriculture, such as biostimulants or biofertilizers. However, although seventy percent of farmers expressed their willingness to use them, results also showed that only 32% of farmers using microalgae-derived applications have obtained satisfactory results. We call the urgent need for new communication strategies based on transdisciplinary approaches that increase farmers’ knowledge around the multiple microalgae-derived products and applications in agriculture.